Technical challenges and outlook of underground hydrogen storage in depleted oil and gas reservoirs - Xiaoming LUO; Zihan JIA; Hongyang ZHANG (You-qi chuyun)
Hydrogen, as an efficient energy carrier and clean fuel, has a demand for large-scale storage. At present, the underground hydrogen storage (UHS), in types of salt caverns, depleted oil and gas reservoirs and aquifers, is the most feasible solution balancing the storage security and economy. Specifically, UHS in the depleted oil and gas reservoirs is most promising among the three types. Herein, the particularity of UHS was discussed by comparing the difference of physical properties among H2, CH4 and CO2. In particular, the technical challenges and coping strategies for UHS in depleted oil and gas reservoirs were overviewed: (1) For the gas leakage caused by unstable displacement, seepage and diffusion, efforts should be made to control the gas injection rate, optimize the scheme of injection-production and cushion gas arrangement, and study the caprock breakthrough pressure, the surface interface characteristics and the flow and mass transfer mechanism. (2) For the hydrogen-consuming geochemical reaction and microbial catalysis, the strata with highly hydrogen-sensitive minerals, ions and microorganisms should be excluded from UHS potential sites to prevent unacceptable H2 consumption. (3) To cope with the integrity failures of traps and artificial materials, the risk of formation damage and gas leakage should be evaluated considering the macroscopic and microscopic deformation and fracture evolution characteristics of the formation. Besides, appropriate materials should be selected to enhance the resistance of artificial facilities to corrosion and hydrogen embrittlement. Finally, the directions of research on UHS technology were pointed out, including the research on H2 loss mechanism under multi-scale and multi-field coupling, the numerical simulation study on-site scale of UHS, and the gas migration and leakage monitoring technology in UHS. Generally, this research could provide a reference for promoting the engineering practice of UHS.